2018
DOI: 10.15421/021885
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the Ukrainian black-pied dairy breed with the genome BoLA-DRB3

Abstract: The second exon of the BoLA-DRB3 gene has the highest level of polymorphism among all studied loci of the major histocompatibility complex (MHC) in cattle, which allows it to be used for studying population-genetic structure and assessing the level of biodiversity of populations or comparing the biodiversity of particular herds. According to the results of typing the blood samples of 293 cows using the method of PCR-RLFP, we determined allele frequencies of the BoLA-DRB3 gene for the Ukrainian black-pied dairy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Studies have shown that haplotype diversity can substantially reveal the amount of phenotypic variance at a particular genomic region (36). It is important to study the genetic basis of the mechanisms for the evolution and maintenance of genetic variation in the innate immune system among or within species, since the functions of the IFNA genes are critical for triggering the immune response to a viral infection or other immune pathogenic states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that haplotype diversity can substantially reveal the amount of phenotypic variance at a particular genomic region (36). It is important to study the genetic basis of the mechanisms for the evolution and maintenance of genetic variation in the innate immune system among or within species, since the functions of the IFNA genes are critical for triggering the immune response to a viral infection or other immune pathogenic states.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed the first evidence of IFNAA haplotypebase framework in cattle, which could be used in association studies of different disease phenotypes. Several reports have shown that association studies with haplotype analysis are a powerful tool to elucidate genetic mechanism of variations underlying complex disease traits (36,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Найбільш поширеним був алель BoLA-DRB3.2*24 з Р(А) = 0,181. Репертуар найбільш поширених варіантів характерний для голштинської породи [21].…”
unclassified